The aesthetic value of reef fishes is globally mismatched to their conservation priorities - Juliette Langlois; François Guilhaumon; Florian Baletaud; Nicolas Casajus; Cédric De Almeida Braga; Valentine Fleuré; Michel Kulbicki; Nicolas Loiseau; David Mouillot; Julien P. Renoult; Aliénor Stahl; Rick D. Stuart Smith; et al. (PLoS Biology, 2022)
Reef fishes are closely connected to many human populations, yet their contributions to society are mostly considered through their economic and ecological values. Cultural and intrinsic values of reef fishes to the public can be critical drivers of conservation investment and success, but remain challenging to quantify. Aesthetic value represents one of the most immediate and direct means by which human societies engage with biodiversity, and can be evaluated from species to ecosystems. Here, we provide the aesthetic value of 2,417 ray-finned reef fish species by combining intensive evaluation of photographs of fishes by humans with predicted values from machine learning. We identified important biases in species’ aesthetic value relating to evolutionary history, ecological traits, and International Union for Conservation of Nature (IUCN) threat status. The most beautiful fishes are tightly packed into small parts of both the phylogenetic tree and the ecological trait space. In contrast, the less attractive fishes are the most ecologically and evolutionary distinct species and those recognized as threatened. Our study highlights likely important mismatches between potential public support for conservation and the species most in need of this support. It also provides a pathway for scaling-up our understanding of what are both an important nonmaterial facet of biodiversity and a key component of nature’s contribution to people, which could help better anticipate consequences of species loss and assist in developing appropriate communication strategies. The most beautiful reef fish are tightly packed into small regions of both the phylogenetic tree and the ecological trait space of the world’s reef fish fauna and are less threatened than unattractive fish. This study highlights likely important mismatches between potential public support for conservation and the species most in need of this support.